Association between body mass index and outcomes in Japanese living kidney transplant recipients: The role of sex differences. (9th June 2016) - Okumi, Masayoshi; Unagami, Kohei; Tachibana, Hidekazu; Hirai, Toshihito; Ishida, Hideki; Tanabe, Kazunari; ,
Abstract : Objective: To evaluate the impact of pretransplant body mass index on graft failure and mortality in Japanese patients undergoing living kidney transplant. Methods: A cohort of 888 living kidney transplant recipients who received standard immunosuppressive therapy between 2000 and 2013 were identified from the Japan Academic Consortium of Kidney Transplantation database. Pretransplant body mass index was divided into three categories according to the following tertiles: <19.4, 19.5–22.2 and ≥22.3 kg/m 2 . A multivariable time‐to‐event analysis was carried out. Results: Estimated hazard ratios of the body mass index effects regarding graft failure were 1.62 (95% confidence interval 0.83–3.18) for the first tertile and 2.20 (95% confidence interval 1.24–3.90) for the third tertile. Patient mortality was 1.21 (95% confidence interval 0.32–4.54) for the first tertile and 1.52 (95% confidence interval 0.56–4.13) for the third tertile. In a subgroup analysis, the effects of body mass index according to sex were substantially heterogeneous ( P = 0.029 for interaction). Pretransplant body mass index had a non‐linear J‐shaped association with graft failure that resulted from qualitative interaction between body mass index and the recipient's sex. Conclusions: Sex differences and interaction effects must be considered when evaluating the effects of pretransplant body mass index on post‐transplant outcomes in Japanese patients undergoing living kidney transplant.